Breakthrough Invention Performance of Multispecialized Clustered Regions in Europe. (15th March 2021) - De Noni, Ivan; Belussi, Fiorenza
Abstract: The regional literature of the last decades has been characterized by an extended debate on the role of regional diversification compared to specialization as a driver of innovation. In this context, the smart specialization framework has recently developed a balanced perspective by emphasizing the role of related diversification of the regional portfolio. Nevertheless, most of the empirical research on the topic has investigated the intensity rather than relevance of technological progress. This article contributes to this framework by exploring the breakthrough performance of European regions. In particular, by focusing on industry–region pairs in place of regions as a whole, the article attempts to claim that the ability to produce breakthrough inventions is higher in multispecialized clustered regions, since it depends on both the specialization of industries and the technological relatedness to the clustered industries of the region. The implications at the level of regional policies are huge, given that the potential of unrelated competitive industries might remain largely unexploited, and diversification in related, although not competitive, industries risks being unprofitable.